Discovery of Novel, Potent, and Specific Cell‐Death Inducers in the Jurkat Acute Lymphoblastic Leukemia Cell Line. Issue 10 (12th August 2015) - Carosati, Emanuele; van den Höfel, Natascha; Reif, Manuela; Randazzo, Giuseppe Marco; Stanitzki, Bettina; Stevens, Julia; Gabbert, Helmut E.; Cruciani, Gabriele; Mannhold, Raimund; Mahotka, Csaba
Abstract The limited clinical efficacy of many cancer therapeutics has initiated intense research efforts toward the discovery of novel chemical entities in this field. In this study, 31 hit candidates were selected from nearly 800 000 database compounds in a ligand‐based virtual screening campaign. In turn, three of these hits were found to have (sub)micromolar potencies in proliferation assays with the Jurkat acute lymphatic leukemic cell line. In this assay, the three hits were found to exhibit higher potency than clinically tested cell‐death inducers (GDC‐0152, AT‐406, and birinapant). Importantly, antiproliferative activity toward non‐cancer peripheral blood mononuclear cells (PBMCs) was found to be marginal. Further biological characterization demonstrated the cell‐death‐inducing properties of these compounds. Biological testing of hit congeners excluded a nonspecific, toxic effect of the novel structures. Altogether, these findings may have profound relevance for the development of clinical candidates in tumor therapy.